Role of C-reactive protein, lactate dehydrogenase, Vitamin D, and interleukin-6 in the prognosis of COVID-19 – A retrospective study in a tertiary care hospital in Tamil Nadu - Sivakumar, J; Anitha, G; Ponnazhagan, K (Asian Journal of Medical Sciences, 2022)
Background: SARS-COV-2 is also known as coronavirus causes an infectious disease has caused a global concern due to its pandemic nature. In India, nearly 36 million cases and 5.1 lakh deaths have been recorded so far. Laboratory biomarkers play an important role in improving the clinical situational awareness by predicting risk stratification and by discriminating between severe and non-severe cases. There is no sufficient information available regarding the role of C-reactive protein (CRP), lactate dehydrogenase (LDH), Vitamin D, and interleukin-6 (IL-6) in the prognosis of COVID-19 patients in Southern part of India. Aims and Objectives: We aim to retrospectively analyze CRP, LDH, Vitamin D, and IL-6 in COVID-19 patients. Materials and Methods: The observational and retrospective study was carried out from the case records of 103 patients from November 2021 to February 2022 in which CRP, LDH, Vitamin D, IL-6, COVID-19 Reporting and Data System (CO-RADS), and CT sore were analyzed during admission and follow-up period in the hospital. Mean, mean difference, standard deviation, standard error difference, and P value were calculated. P<0.05 was considered to be significant. Results: CRP, LDH, IL-6, Vitamin D, CO-RADS, and CT score were decreased during the follow-up period when these levels were compared at the time of admission in the hospital, while there is an increase in Vitamin D levels during the follow-up period. Conclusion: The use of reliable and easy to use assays such as CRP, LDH, Vitamin D, and IL-6 plays an important role in the diagnosis and prognosis of COVID-19.